Study on the Feasibility of Construction of Logung Dam in Kudus Regency - Tri Hartadi; Soedarsono Soedarsono; Moch Faiqun Ni'am (International Conference on Coastal and Delta Areas, 2017)
The availability of water in the increasingly rare dry season and the tendency of floods in the rainy season, is a problem that can not be solved completely in various regions in Indonesia. The construction of reservoirs is generally aimed at helping to overcome the problem of increasing water resources needs from time to time. The area of Kudus Regency is an area with relatively limited water resources. Therefore it is necessary to plan the construction of Logung dam in the hope that the surrounding ground water can be maintained, the forest can be grown, and in the end can preserve the existing water source. The aim of this research is to get an overview of Logung Dam plans that are economically feasible both from cost aspect and benefit aspect. To find out the feasibility of Construction of Logung Dam in Kudus Regency, Net Present Value (NPV), Internal Rate of Return (IRR) and Net Benefit Cost Ratio (Net B / C) will be performed. Keywords: economic feasibility, Logung dam, Kudus regency